A Comprehensive Survey of Phishing Email Detection and Protection Techniques. Issue 4 (4th July 2022) - Kumar Birthriya, Santosh; Jain, Ankit Kumar
ABSTRACT: E-Mails are commonly used as a medium of communication for personal and pro- fessional purposes. Information shared via mail is also sensitive and private, such as financial information, credit records, login data, and so on. This makes them useful to cyber attackers who can exploit this knowledge for illegal purposes. Phishing is a technique used by fraudsters to gain confidential data from users by alleging to be from known sources. In a phished e-mail, the sender can encourage users to provide private in- formation under false premises. Phishing e-mails have also been frequently used in financial institutions and consumer fraud. This paper discusses an overview of dif- ferent techniques for phishing e-mail detection and protection currently used in e-mail filtering. A comparative analysis and review of these techniques are carried out. This survey provides an understanding of the phishing detection issue, its present space for a solution, and its future directions for study.